Toward a Global Horizontal and Vertical Elastic Load Deformation Model Derived from GRACE and GNSS Station Position Time Series. Issue 4 (18th April 2018) - Chanard, Kristel; Fleitout, Luce; Calais, Eric; Rebischung, Paul; Avouac, Jean‐Philippe
Abstract: We model surface displacements induced by variations in continental water, atmospheric pressure, and nontidal oceanic loading, derived from the Gravity Recovery and Climate Experiment (GRACE) for spherical harmonic degrees two and higher. As they are not observable by GRACE, we use at first the degree‐1 spherical harmonic coefficients from Swenson et al. (2008, https://doi.org/10.1029/2007JB005338 ). We compare the predicted displacements with the position time series of 689 globally distributed continuous Global Navigation Satellite System (GNSS) stations. While GNSS vertical displacements are well explained by the model at a global scale, horizontal displacements are systematically underpredicted and out of phase with GNSS station position time series. We then reestimate the degree 1 deformation field from a comparison between our GRACE‐derived model, with no a priori degree 1 loads, and the GNSS observations. We show that this approach reconciles GRACE‐derived loading displacements and GNSS station position time series at a global scale, particularly in the horizontal components. Assuming that they reflect surface loading deformation only, our degree‐1 estimates can be translated into geocenter motion time series. We also address and assess the impact of systematic errors in GNSS station position time series at the Global Positioning System (GPS) draconitic period and its harmonics on the comparison between GNSS and GRACE‐derived annual displacements. Our results confirm that surface mass redistributions observed by GRACE, combined with an elastic spherical and layered Earth model, can be used to provide first‐order corrections for loading deformation observed in both horizontal and vertical components of GNSS station position time series. Key Points: We model surface horizontal and vertical displacements induced by mass variations derived from GRACE at a global network of GNSS stations We estimate the degree 1 deformation field from comparing GRACE‐derived model and GNSS observations Results show that GRACE with an elastic Earth model, can provide loading horizontal and vertical deformation correction models for GNSS